دراسة مقارنة في إطار الأدب الإسلامي بين كتاب "منهج الفن الإسلامي" وكتاب "الرسالة إلى المسلمين - Comparative study in Islamic Literature between “Manhaj al-Fann al-Islami (Principles of Islamic Art)” and “Al-Risalah ila al-Muslimin (A Letter to Muslim) - Mohd Sanadi, Aida Hayati; Ahmad Safian, Nursafira (KOLEJ UNIVERSITI ISLAM ANTARABANGSA SELANGOR (KUIS), 2019)
تناول هذا البحث بالدراسة المقارنة بين مفهوم الأدب الإسلامي عند محمد قطب في كتابه "منهج الفن الإسلامي" وسيد نقيب العطاس في كتابه "الرسالة إلى المسلمين". ومن أهداف هذا البحث إعطاء فكرة عامة عن الكاتبين وإبراز تقديمهما لمفهوم الأدب الإسلامي. ويعدّ الكاتبان من الأدباء الذين تناقشوا قضايا عصرهم في ضوء الإسلام ومبادئه، وقدّموا حلولاً لمشاكل مختلفة في مجال الفكر والأدب. وقد تناول الكاتبان مفهوم الأدب الإسلامي بناء على العقيدة الصحيحة التي تسعى إلى إعداد الإنسان الصالح والمجتمع الصالح. ويسير البحث على المنهجين: الوصف والتحليل والمقارنة، وذلك من خلال تحليل آرائهما حول الأدب الإسلامي في الكتابين المذكورين، قبل أن تقوم الدراسة بالمقارنة بين مفهوم الكاتبين للأدب الإسلامي لمعرفة أوجه الاتفاق والاختلاف بينهما. لقد طرح محمد قطب مصطلح "الفن الإسلامي" بينما استخدم العطاس مصطلح "الأدب الإسلامي" في كتابه. وبجانب ذلك، ذكر محمد قطب أن الأدب الإسلامي هو الفن الذي يرسم صورة الوجود من زاوية التصور الإسلامي لهذا الوجود، وهو التعبير الجميل عن الكون والحياة والإنسان، من خلال تصور الإسلام للكون والحياة والإنسان. أما العطاس فقد أيّد الرأي الغربي؛ حيث إنه رأى أن الأدب ينقسم إلى القسمين، أولهما: الأدب الذي يدل على الفلسفة والجمال (aesthetics)، وثانيهما: الأدب الذي يعتني بالمحتوى المعنوي؛ إذ ظهر ذلك في الجنس الأدبي الشعري (literature). ثم، يوسّع العطاس هذا المفهوم وأعطى للأدب معنىً جديدًا عن طريق القيم العقلية الصادقة. ******************************************************************************************* This study compare the concept of Islamic literature presented by Muhammad Qutb in his book, “Manhaj al-Fann al-Islami (Principles of Islamic Art)” and Syed Naquib Al-Attas in his book, “Al-Risalah ila al-Muslimin (A Letter to Muslim)”. The objective of this study is to give a general account on these two scholars and highlight their contributions to the conceptualization of Islamic literature. They are among prominent scholars who discuss extensively various contemporary issues from the view of Islamic perspective. They addressed the concept of Islamic literature in accordance with the correct belief that are useful in producing righteous human and society. The researchers make use in the study descriptive, analytical and comparative methods. The researchers analyze the concept of Islamic literature discussed in the books mentioned as well as make comparison between both of their views, highlighting theaspects of similarities and differences. Muhammad Qutb proposed the phrase “Islamic Art” while Al-Attas used the term “Islamic Literature” in respective writings. Apart from that, Muhammad Qutb stated that Islamic literature is the art that rules the picture of existence from the view of Islamic perspective and it is a fine expression about the existence and lives of humans. Meanwhile, Al-Attas are likely endorsed the Western view when he mentioned that literature is divided into two; firstly, it depicts the philosophy and aesthetics. Secondly, it defined and emerged in the type of literature. Al-Attas also widened the concept of literature using genuine intellectual approach.